Origin, evolution, dispersal and global population genetic structure of Carlavirus sigmasolani - Lei, Jianlin; Liang, Beibei; Yang, Hongwei; Zhang, Bo (Frontiers in Plant Science, 2025)
Carlavirus sigmasolani (Potato virus S, PVS) is a globally distributed plant virus infecting cultivated potato (Solanum tuberosum), causing yield losses and reduced tuber quality in the host crop, yet its evolutionary history, global dissemination and population genetic structure remain incompletely understood. In this study, we conducted comprehensive phylogenetic and Bayesian phylogeographic analyses of PVS using all available complete genome and coat protein (CP) gene sequences from 35 countries. Genome-based phylogenetic reconstruction identified four major phylogroups (I–IV), with Phylogroup I comprising only Colombian isolates and Phylogroup IV showing the broadest geographic distribution. In contrast, CP gene-based analyses revealed seven phylogroups (I–VII), including regionally restricted Phylogroups V (Colombia) and VI (Ecuador), and the globally dominant Phylogroup VII. A time-scaled Bayesian phylogenetic framework estimated a mean substitution rate of 3.11 × 10-4 substitutions/site/year (95% HPD: 2.19 × 10-4–4.07 × 10-4), and dated the most recent common ancestor (tMRCA) of PVS to approximately 1296 (95% HPD: 964–1578). Phylogeographic analysis based on CP gene sequences suggests that Ecuador is a likely center of origin for PVS, with intercontinental dissemination beginning in the 16th century and markedly accelerating during the 19th and 20th centuries. Iran and China were identified as major secondary hubs during this period, while Europe and the United States also contributed to global dissemination as important intercontinental transmission centers during the 20th and 21st centuries. Population genetic analyses indicated that South America retains the highest diversity, reinforcing its status as the center of origin, while the markedly lower diversity in Africa and Oceania suggests more recent introductions coupled with restricted gene flow. These data improve our understanding of PVS evolution, spread and population structure, supporting the development of effective monitoring and control strategies.